Monteiro Lobato acontece na América: análise de duas transposições do conto "O Engraçado Arrependido" de Monteiro Lobato para o idioma inglês, respectivamente, em 1925 e 1947 e a relação intelectual do crítico literário Isaac Goldberg com o autor brasileiro - Carter, Rosemary de Paula Leite (2012)
This thesis has the purpose to investigate Monteiro Lobato's expectations and interests in relation to the publishing of his literary works in North-America with a broader number of readers and a larger book circulation. We will specially focus on Brazilian Short Stories, Series Little Blue Books, nº 733, published by Haldeman-Julius Company in 1925. The pioneer role of the North-American literary critic Isaac Goldberg (1887-1938) as a go-between and organizer of some Brazilian literary works of Art as well as of some Lobato's earliest published material in The United States of America will also be pursued. We also aim to examine the accomplishments of two transpositions of the short story O Engraçado Arrependido into English. The literary works are: "The Penitent Wag" in Brazilian Short Stories, Little Blue Book nº 733, by Haldeman Julius Company (1925) and The Funny Man Who Repented published in A World Of Great Stories by Crown Publisher(1947). In order to attain this target we intend to compare the text in Portuguese (9th edition, Urupês, 1923), with the mentioned transpositions into English in 1925 and 1947.